The Impact of Game-Based Activities on German Language Learning - Saodatjon Bobokhonova (Academicia Globe: Inderscience Research, 2026)
In recent decades, language education has increasingly incorporated innovative pedagogical approaches designed to enhance student engagement and learning outcomes. Among these approaches, game-based learning has gained considerable attention as an effective strategy for promoting active participation and motivation in foreign language classrooms. This study investigates the impact of game-based activities on learning German as a foreign language (GFL). The research explores how interactive learning environments that incorporate educational games influence learners’ motivation, communicative competence, and vocabulary retention. A mixed-method research design was employed involving 72 undergraduate students enrolled in introductory German language courses. The experimental group participated in structured game-based activities including vocabulary games, role-play simulations, collaborative tasks, and digital quiz platforms, while the control group received traditional instruction. Data were collected through language proficiency tests, classroom observations, and learner questionnaires. The findings indicate that students exposed to game-based learning demonstrated significantly higher motivation levels, improved vocabulary retention, and greater speaking confidence than those taught through traditional methods. These results support previous research highlighting the positive effects of gamification on language learning outcomes. The study concludes that game-based learning represents an effective pedagogical tool for improving German language instruction and creating interactive learner-centered classrooms